2020
DOI: 10.1186/s12967-020-02581-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of circulating lncRNAs as potential biomarkers in chronic respiratory diseases

Abstract: Background In the present study the blood expression level of inflammatory response and autoimmunity associated long non-coding RNAs (lncRNAs) were compared in patients with different chronic respiratory diseases and investigated whether they could be used as biomarkers in these diseases. Methods In the discovery cohort, the gene expression level of 84 lncRNAs were measured in the blood of 24 adult patients including healthy controls and patients with asthma and COPD. In the replication cohort the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Although there have been clinical trials to detect the differential expression of lncRNAs in the peripheral blood of patients with asthma ( Gál et al, 2020 ; Zheng et al, 2020 ), there are many lncRNAs that have not been annotated. Finding other lncRNAs that may play a key role in asthma is therefore important, and may contribute to a better understanding and treatment of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been clinical trials to detect the differential expression of lncRNAs in the peripheral blood of patients with asthma ( Gál et al, 2020 ; Zheng et al, 2020 ), there are many lncRNAs that have not been annotated. Finding other lncRNAs that may play a key role in asthma is therefore important, and may contribute to a better understanding and treatment of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of lncRNAs have been functionally annotated. Although studies have reported some differences in lncRNAs in asthma patients during both childhood ( Zheng et al, 2020 ) and adulthood ( Gál et al, 2020 ), there are many lncRNAs with an unclear relationship to asthma that require investigation and annotation. In the present study, we aimed to perform whole transcriptome sequencing in patients with asthma using second-generation high-throughput sequencing to identify dysregulated lncRNAs that are associated with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of studies have confirmed the anomalous expression of lncRNA in lung tissue of COPD, and some lncRNA showed obvious and specific expression, which will help to find early biomarkers and drug treatment targets related to COPD. In an investigation about chronic respiratory diseases, the expression of OIP5-AS1 is elevated in COPD patients compared with patients with asthma [ 33 ]. The current study indicated that the levels of OIP5-AS1 were elevated in smokers and smokers with COPD, which provided that OIP5-AS1 may be used as an early biomarker of COPD occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been done to determine whether lncRNAs can be used as biomarkers for chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD) 77,78 . OIP5‐AS1 shows differential expression in models of asthma relative to controls, 79,80 and as such, it has been found to have discriminative power as a potential biomarker for asthma 77,79 .…”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%
“…Previous studies have been done to determine whether lncRNAs can be used as biomarkers for chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD) 77,78 . OIP5‐AS1 shows differential expression in models of asthma relative to controls, 79,80 and as such, it has been found to have discriminative power as a potential biomarker for asthma 77,79 . Its functions in apoptosis regulation and inflammatory processes in multiple cell types, and the association of these characteristics with bronchial asthma, also justified studies of OIP5‐AS1 in asthma.…”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%